The METABANK score: A clinical tool to predict survival after stereotactic radiotherapy for oligometastatic disease. (April 2019) - Van den Begin, Robbe; Engels, Benedikt; Collen, Christine; de Vin, Tessa; Defauw, Arne; Dubaere, Emilie; Barbé, Kurt; De Ridder, Mark
Graphical abstract: Abstract: Background and purpose: Stereotactic radiotherapy (SRT, SBRT) is widely used in oligometastatic cancer, but the heterogeneity of the population complicates estimation of the prognosis. We investigated the role of different clinical and inflammatory parameters. Materials and methods: We included all patients treated with SRT for 1–5 oligometastases between 2003 and 2017 in our center. Patients were randomized between a model training set (2/3) and a separate validation set (1/3). A Cox regression model was built, validated and risk points were attributed to the resulting parameters. Results: 403 patients received SRT for 760 metastases. Treated sites were mainly lung, liver, nodal areas, and brain. Most common primaries were colorectal and lung cancer. Median follow-up for living patients reached 42 months and median overall survival (MS) was 26.6 months (95% CI 23.8–29.3). Five independent adverse factors were discriminated: male sex, synchronous timing of oligometastases, brain metastasis, non-adenocarcinoma histology, KPS <80. A risk score is formed by summation of the points of each factor (M:4, T:2, B:7, N:7, K:8). Four risk groups were defined: (1) 0–2 points: MS 41.2 months (95% CI 30.2–52.3); (2) 3–8 points: 29.3 months (24.6–34.0); (3) 9–13 points: 17.4 months (10.1–24.7), and (4) 14–28 points: 7.9 months (5.5–10.3). Conclusion: We propose a prognostic score applicable in a variety of primary tumors and disease locations, including presence of brain metastases. The nomogram and risk groups can be used to stratify patients in new trials and to support individualized care for oligometastatic patients. An online calculator will become available at predictcancer.org.